Conservation Tillage Peanut Production - David L. Wright; James J. Marois; Jimmy R. Rich; Richard K. Sprenkel; Elmo B. Whitty (EDIS)
This document is SS-AGR-185, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published October 2002.